PENGEMBANGAN MEDIA PEMBELAJARAN LIVEWORKSHEETS INTERAKTIF DALAM MENINGKATKAN HASIL BELAJAR IPS - Regina Purba; M. Taufik; Ujang Jamaludin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2022)
The background of this research is related to the students' need for learning media. Learning media is needed in learning as an intermediary for delivering information. The use of learning media that is still minimal is a topic that will be raised. The purpose of this study was (1) to determine the feasibility of the Liveworksheets learning media, (2) to determine student responses to the Liveworksheets learning media, (3) to determine the improvement of student learning outcomes towards Liveworksheets learning. media. The target of this research is the fifth grade students of SDN Sukasari 6. This study uses research and development methods with the Borg and Gall in development model (Sugiyono 2016:298), namely: potential problems, information collection, product design, product validation, product revision, trial product, end result. Based on the results of data analysis, there is an average instrument validation of 85.45%, media validation 79%, material validation 84%, language validation 76%. The results of the small-scale students' pretest and posttest were 10 people, 84.50 and 98.60. The results of the small-scale student response test 10 people 90.05%. Response data 96.3%. The average pretest using 21 students was 62.10. The average posttest was 90.05%. So to find out the increase in learning outcomes is calculated by the N-Gain test with a score of 0.7571 in the high category.